Neutrophilic inflammation promotes SARS-CoV-2 infectivity and augments the inflammatory responses in airway epithelial cells - Calvert, Ben A.; Quiroz, Erik J.; Lorenzana, Zareeb; Doan, Ngan; Kim, Seongjae; Senger, Christiana N.; Anders, Jeffrey J.; Wallace, Wiliam D.; Salomon, Matthew P.; Henley, Jill; Ryan, Amy L. (Frontiers in Immunology, 2023)
Introduction In response to viral infection, neutrophils release inflammatory mediators as part of the innate immune response, contributing to pathogen clearance through virus internalization and killing. Pre- existing co-morbidities correlating to incidence to severe COVID-19 are associated with chronic airway neutrophilia. Furthermore, examination of COVID-19 explanted lung tissue revealed a series of epithelial pathologies associated with the infiltration and activation of neutrophils, indicating neutrophil activity in response to SARS-CoV-2 infection. Methods To determine the impact of neutrophil-epithelial interactions on the infectivity and inflammatory responses to SARS-CoV-2 infection, we developed a co-culture model of airway neutrophilia. This model was infected with live SARS-CoV-2 virus the epithelial response to infection was evaluated. Results SARS-CoV-2 infection of airway epithelium alone does not result in a notable pro-inflammatory response from the epithelium. The addition of neutrophils induces the release of proinflammatory cytokines and stimulates a significantly augmented proinflammatory response subsequent SARS-CoV-2 infection. The resulting inflammatory responses are polarized with differential release from the apical and basolateral side of the epithelium. Additionally, the integrity of the \epithelial barrier is impaired with notable epithelial damage and infection of basal stem cells. Conclusions This study reveals a key role for neutrophil-epithelial interactions in determining inflammation and infectivity.